Efektivitas Terapi Antihipertensi Pada Kasus Krisis Hipertensi di Instalasi Gawat Darurat RSUD Ulin Banjarmasin - Evita Peron Yoewono; Rina Saputri; Rifa’atul Mahmudah (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
ABSTRACT Background: Hypertension crisis is a case of disease that often occurs, if not handled properly will cause comlication and death. This study was conducted to determine effective therapies in dealing with hypertensive crises so as to minimize the occurrence of complication and death in patients experiencing hypertensive crises Method: The research method is a prospective cohort. Data analysis using Pair T-Test and ANOVA, analytic analysis with evidence based medecine principles. Consists of 11 urgent hypertension samples and 9 emergency hypertension samples. Results: The results of the study for the case of hypertension urgency there are 6 therapeutic groups including furosemide, nicardipine, amlodipine, candesartan + amlodipine, clonidine and furosemide + nicardipine, but the therapy used is not in accordance with the guidelines but there are 2 groups of therapies that can reduce blood pressure including furosemide + nicardipine and clonidine, while for the case of emergence hypertension, there are 5 groups of therapies including nicardipine, amlodipine + nicardipine, furosemide, furosemide + candesartan + amlodipine and furosemide + candesartan + amlodipine + clonidine, the result is that nicardipine is a therapy that is in accordance with the guideline and the therapy is in accordance with the guideline and is in accordance with the guideline therapeutic target in lowering blood pressure. Conclusion: The use therapy is not in accordance with the guidelines for patients with hypertensive urgency cases, but is able to lower the patient’s blood pressure, whereas for patients with hypertensive emergencies the effective therapy is nicardipine. Keywords: Blood Pressure, Effectiveness, Hypertensive Crisis, Urgency Hypertension, Emergency Hypertension.